Seasonal and long-term vegetation dynamics from 1-km GIMMS-based NDVI time series at Mt. Kilimanjaro, Tanzania - Florian Detsch; Insa Otte; Tim Appelhans; Andreas Hemp; Thomas Nauss (PANGAEA, 2022)
This dataset consists of GeoTIFF fille for GIMMS NDVI downscaled record (1982–2011) that was resampled from 8 km to 1 km spatial resolution.